2022
DOI: 10.1177/00302228211070400
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Death Anxiety Among Iranian Patients With Cancer

Abstract: Death anxiety in cancer patients can cause and exacerbate mental disorders and affect the healing process and survival. In this study, percentage score of death anxiety among Iranian cancer patients was reported. The databases of Scopus, PubMed, ISI, MagIran, and Scientific Information Database were searched and 396 articles were retrieved. Twenty-three eligible studies were included in the analysis considering the inclusion criteria. Heterogeneity among selected studies was assessed through the Cochrane Q tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…In addition, 72.9% of patients with breast cancer reported high levels of death anxiety. According to Shakeri et al ( 3 ), 67.5% of patients with breast cancer experienced death anxiety =. Another study conducted in Iran by Masror Roudsary et al ( 9 ) revealed that 79% of patients with breast cancer experienced death anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, 72.9% of patients with breast cancer reported high levels of death anxiety. According to Shakeri et al ( 3 ), 67.5% of patients with breast cancer experienced death anxiety =. Another study conducted in Iran by Masror Roudsary et al ( 9 ) revealed that 79% of patients with breast cancer experienced death anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, the global breast cancer incidence in 2022 was 2.3 million, with 670,000 deaths ( 1 ). Cancer typically elicits psychological reactions characterized by traumatic stress ( 2 ) and requires treatment with extreme caution due to the negative connotation associated with the term “cancer” ( 2 , 3 ). Patients who are diagnosed with cancer experience profoundly intense psychological reactions, including a sense of impending death.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations